1982
DOI: 10.1113/jphysiol.1982.sp014344
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sodium replacement on the responses of toad rods

Abstract: SUMMARY1. We have investigated the effects of Na+ substitution on the membrane potential and light responses of rods in the superfused retina of the toad, Bufo marinus.2. When all of the Na+ in the Ringer was replaced with Li+, the effects on the rods depended upon the external free Ca2+ concentration ([Ca2+] 5. Substitution of Na+ with K+ in low Ca2+ produced a complete suppression of the responses. However, it was still possible to measure large light-induced changes in rod input resistance. 6. Substitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…Although the T. D. LAMB, H. R. MATTHEWS AND V. TORRE larger responses here were no longer within the linear range this fact does not invalidate our finding. The responses remained roughly linear with intensity, and no sign was found of the superlinearity observed previously using reduced extracellular calcium concentration Bastian & Fain, 1982;Owen & Torre, 1983). The main effect of any departure from linearity would simply be to underestimate the magnitude of the increase in sensitivity which occurs in the presence of BAPTA.…”
Section: Patch-pipette Solutionsmentioning
confidence: 54%
“…Although the T. D. LAMB, H. R. MATTHEWS AND V. TORRE larger responses here were no longer within the linear range this fact does not invalidate our finding. The responses remained roughly linear with intensity, and no sign was found of the superlinearity observed previously using reduced extracellular calcium concentration Bastian & Fain, 1982;Owen & Torre, 1983). The main effect of any departure from linearity would simply be to underestimate the magnitude of the increase in sensitivity which occurs in the presence of BAPTA.…”
Section: Patch-pipette Solutionsmentioning
confidence: 54%
“…Recently, however, Fain & Lisman (1981) and Bastian & Fain (1982) reported that when external Ca2+ is buffered to about 10-8 M, voltage responses can be recorded when Na+ is substituted for Li+. Current responses to light have been recorded when Na+ was completely replaced by choline in low Ca2+ solutions (Yau et al 1981).…”
Section: Capo Villa and Othersmentioning
confidence: 99%
“…Evidence that this is indeed the case comes from studies in which Li+ is substituted for Na+ in the perfusate. When the superfusate [Ca2+1] is less than or equal to 10-7 M, Li+ may be substituted for Na+ without eliminating the photoresponse (solutions L to 0) (Fain & Lisman, 1981;Yau et al 1981;Bastian & Fain, 1982b (Bastian & Fain, 1982b; but see Yau et al 1981).…”
mentioning
confidence: 99%